Literacy HR Mapping based on Spider Mapping Web in Accelerating Sustainable Development Goals (SDGs) 2025 in the Era of Society 5.0 - Khalilullah, M. (Instructional Development Journal, 2023)
This research aims to gain insight into individual understanding and views regarding sustainable development issues, with a focus on Sustainable Development Goals (SDGs). We conducted a series of interviews with diverse respondents to gain a deeper understanding of people's awareness of the SDGs, as well as the factors that influence their perceptions and efforts to achieve sustainable goals. The research results show variations in understanding of the SDGs among respondents, with an emphasis on a multidimensional approach, the role of government, cross-sector collaboration, technological innovation, and community education as key elements in supporting sustainable development. This research provides a more comprehensive understanding of how communities can contribute to achieving the SDGs and the factors that influence their views